Предмет: Математика,
автор: Аноним
Решите уравнения:
1) 10-2*(3х+5)=4*(х-2)
2) 7*(х-5)+1=2-3*(2х-1)
3) 5*(2х-3)-2*(3-2х)=15-6*(х+1)
Ответы
Автор ответа:
0
1) 10-2*(3х+5)=4*(х-2)
10 - 6х - 10 = 4х - 8
- 6х - 4х = - 8 - 10
-10х = - 18
х = 1,8
2) 7*(х-5)+1=2-3*(2х-1)
7х - 35 + 1 = 2 - 6х + 3
7х +6х = 2+3 +35 -1
13х = 39
х = 13
3) 5*(2х-3)-2*(3-2х)=15-6*(х+1)
10х -15 - 6 + 4х = 15 - 6х -6
10х + 4х +6х = 15 - 6 +15 +6
20х = 30
х = 1,5
10 - 6х - 10 = 4х - 8
- 6х - 4х = - 8 - 10
-10х = - 18
х = 1,8
2) 7*(х-5)+1=2-3*(2х-1)
7х - 35 + 1 = 2 - 6х + 3
7х +6х = 2+3 +35 -1
13х = 39
х = 13
3) 5*(2х-3)-2*(3-2х)=15-6*(х+1)
10х -15 - 6 + 4х = 15 - 6х -6
10х + 4х +6х = 15 - 6 +15 +6
20х = 30
х = 1,5
Автор ответа:
0
во втором примере опечатка. ответ 3 а не 13
Автор ответа:
0
1) 10-2*(3х+5)=4*(х-2)
10-6х-10=4х-8
-6х-4х=-8-10
-10х=-18
х=-18:(-10)
х=
2)7*(х-5)+1=2-3*(2х-1)
7х-35+1=2-6х+3
7х+6х=2+3+35-1
13х=39
х=3
3) 5*(2х-3)-2*(3-2х)=15-6*(х+1)
10х-15-7+4х=15-6х-6
10х+4х+6х=15-6+15+7
20х=1
х=0,05
10-6х-10=4х-8
-6х-4х=-8-10
-10х=-18
х=-18:(-10)
х=
2)7*(х-5)+1=2-3*(2х-1)
7х-35+1=2-6х+3
7х+6х=2+3+35-1
13х=39
х=3
3) 5*(2х-3)-2*(3-2х)=15-6*(х+1)
10х-15-7+4х=15-6х-6
10х+4х+6х=15-6+15+7
20х=1
х=0,05
Автор ответа:
0
1)х=1,8
Похожие вопросы
Предмет: Право,
автор: riliaahmetzakirova
Предмет: Математика,
автор: bulaon74
Предмет: Математика,
автор: QwetryX
Предмет: Алгебра,
автор: кура
Предмет: Геометрия,
автор: Zer098